Analysis of Lightning Strike Impulse Strategies in Electricity Distribution Channels Utilizing Mixed Lines - Muhammad Iswal Burhan; Dessy Ana Laila Sari (Buletin Ilmiah Sarjana Teknik Elektro, 2023)
To ensure the operational security of these systems and to give higher quality electricity to all users, it is important to assess the transient behavior of electric power transmission and distribution systems when they are challenged to varied forms like lightning discharges, which in this research is focused to determine the effect by utilizing the mixed line configuration on the impulse voltage of lightning strike on the 20 kV distribution line. This experiment was carried out using sources of data through channel documentation on Makassar City Polda Feeders with an airway length (SUTM) of 7.8 km and a cable channel length (SKTM) of 2 km obtained from PT. PLN (Persero) Makassar Branch and then input into the ATP-EMTP simulation process with either a simulation of 20 and 50 kA strikes at distances of 2.5, 4.5 and 6.5 km with lightning impulses of 1.2/50 and 8/20 µs. configuration of lines at the transition point and also the end of the cable channel depending on the magnitude of the lightning current, the location of the strike, and the lightning impulse. Lightning peak current is proportional to the voltage response at the transition point and the end of the cable, and the effect on lightning impulse peak voltage is generated at the transition point and the end of the cable. According to research results of initial research, the use of mixed channel lines can decrease the impulse voltage is 20 kV distribution lines.